Spatial Variability of Tugbok Clay Loam in a Coconut-Based Farming System (CBFS) in Davao City, Philippines - L. H. Canja; E. P. Paningbatan, Jr.; R. A. Comia; W. C. Cosico; A. J. Alcantara (International Coconut Community Journal, 2009)
The spatial distributions of soil physico-chemical properties were evaluated using variogram and kriging. Kriging as an interpolation technique that used variogram model of observed values was employed to determine values of a soil property at unsampled locations of the study area. Spatial variability map was then generated from the ‘kriged’ data points. Spatial variability analysis using variogram of soil properties showed spatial patterns of various levels. Spatial dependence appeared moderate for soil pH and total K in the topsoil (0-15 cm) and in subsoil (15-30 cm), weak for Bray P in the topsoil but strong for bulk density and organic matter and depth of the topsoil. Spatial variability maps of soil properties showed that the area is strongly acidic, low in organic matter and Bray P, high in total K with low bulk density values at 1.2 to 1.29 (g cm-3) and medium depth topsoil. Spatial variability maps generated by kriging are expected to provide information in precision agriculture in order to make better management decisions, reduce chemical and fertilizer costs through more efficient application, provide more accurate farm records, improve crop yield, and reduce agro-chemical pollution. Precision agriculture relies on the existence of in-field variability.